2004 2nd IEEE International Symposium on Biomedical Imaging: Macro to Nano (IEEE Cat No. 04EX821)
DOI: 10.1109/isbi.2004.1398756
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of brushlet and wavelet denoising methods for nuclear images

Abstract: This paper presents preliminary results on the fusion of denoised PET and SPECT data volumes from brushlet and wavelet thresholding methods. Texture-based brushlet denoising is well suited for enhancement of physiological information while wavelet-based denoising is better suited for enhancement of anatomical contours. A three-dimensional multi-scale edge-based data fusion algorithm is applied to combine enhanced data from these two independent denoising methods. Preliminary results with qualitative evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Conventional filtering operations in frequency domain [2], such as Butterworth filter, are utilized as image denoising methods incorporated in SPECT γ -camera workstations. Although multi-scale denoising methods have been proposed [12][13][14][15][16][17][18][19][20][21][22][23], their performance has not been fully investigated. In this study, the performance of the multi-scale platelet denoising method was compared with the wellestablished Butterworth filter [2,24] applied either as a pre-or post-processing step [36] on images reconstructed without and/or with AC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional filtering operations in frequency domain [2], such as Butterworth filter, are utilized as image denoising methods incorporated in SPECT γ -camera workstations. Although multi-scale denoising methods have been proposed [12][13][14][15][16][17][18][19][20][21][22][23], their performance has not been fully investigated. In this study, the performance of the multi-scale platelet denoising method was compared with the wellestablished Butterworth filter [2,24] applied either as a pre-or post-processing step [36] on images reconstructed without and/or with AC.…”
Section: Discussionmentioning
confidence: 99%
“…Sophisticated methods are required for treating the coefficients in the wavelet domain, such as applying SNRadaptive nonlinear thresholding [12,13] or multiresolution regularization schemes [15][16][17] to noisy wavelet coefficients. Another category of multi-scale denoising methods is based on the estimation of Poisson-distributed data at all resolutions, such as application of a Bayesian multi-scale estimator in a Haar wavelet framework [18] and multi-scale linear hard thresholding supported by wavelet-packet [19] and brushlet [20,21] expansions. Recently, a platelet multi-scale denoising method utilizing maximum penalized likelihood estimation for noise threshold derivation was proposed, with promising performance [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The number of operator combinations were 2 8 (256), 2 12 (4096), 2 12 (4096), 2 18 (262,144), 2 12 (4096), 2 18 (262,144), 2 18 (262,144), and 2 27 (134,217,728). The principle of matrix convolution was used to perform the operation in the morphological structure matrix.…”
Section: Morphological Structure Operationmentioning
confidence: 99%
“…Previous studies have shown that it is possible to remove strike artifacts using interpolation of projections by contouring, but it is challenging to select an interpolated value. For instance, methods such as the Brushlet, Wavelet, and Curvelet transformation can be used to remove strike artifacts from PET images; however, caution should be applied when selecting a threshold [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…and computed tomography. Since it is impractical to cover all of these applications in this paper, the topics of fusion [6][7][8][9][10][11][12][13][14][15][16] was chosen for its value in introduce. analysis.…”
Section: Introductionmentioning
confidence: 99%